2022
DOI: 10.1016/j.jval.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Do Profit Margins of Pharmaceuticals Influence Reimbursement Decisions? A Discrete Choice Experiment Among Dutch Healthcare Decision Makers

Abstract: This study aimed to investigate whether the profit margins of pharmaceuticals would influence the outcome of reimbursement decisions within the Dutch policy context. Methods:We conducted a discrete choice experiment among 58 Dutch decision makers. In 20 choice sets, we asked respondents to indicate which of 2 pharmaceutical treatment options they would select for reimbursement. Options were described using 5 attributes (disease severity, incremental costs per quality-adjusted life-year, health gain, budget imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…In practice, a threshold can serve as a signal of an acceptable price and producers can use this strategically to price their products up to this threshold. Guidelines for CEAs provide little help to decision makers in dealing with strategic price setting, as a crucial assumption in the models behind CEAs is that costs are set exogenously [ 43 ], and thus no distinction is made between price demanded or set by the producer and the cost price of the product [ 44 ]. More attention for ‘pricing below the threshold’, and therefore a fair division of surplus between the producer and society, is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, a threshold can serve as a signal of an acceptable price and producers can use this strategically to price their products up to this threshold. Guidelines for CEAs provide little help to decision makers in dealing with strategic price setting, as a crucial assumption in the models behind CEAs is that costs are set exogenously [ 43 ], and thus no distinction is made between price demanded or set by the producer and the cost price of the product [ 44 ]. More attention for ‘pricing below the threshold’, and therefore a fair division of surplus between the producer and society, is urgently required.…”
Section: Discussionmentioning
confidence: 99%
“…8 ICES, Toronto, ON, Canada. 9 • support for research data, including large and complex data types • gold Open Access which fosters wider collaboration and increased citations maximum visibility for your research: over 100M website views per year…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Hence, given the increased attention for price setting as well as the increased reliance on price negotiations, manufacturers’ costs in relation to prices, or profit margins, could be an explicit part of the deliberations during the appraisal phase, also to justify certain decisions or recommendations. A recent discrete choice experiment among Dutch healthcare decision makers suggested that information on profit margin would influence their reimbursement recommendations when available [ 9 ].…”
Section: Introductionmentioning
confidence: 99%